(untitled) (Research, Society and Development, 2025)
Introduction: Renal dysfunction is a global health issue, associated with high morbidity and mortality. The main renal replacement therapy modalities include peritoneal dialysis, hemodialysis, and hemofiltration, with treatment choice determined by clinical conditions and resource availability. Objective: This study compared continuous hemodialysis (CHD) and intermittent hemodialysis (IHD) in critically ill patients with acute renal failure to assess their impact on mortality rates. Material and Methods: The systematic review included Health Technology Assessment reports, systematic reviews, and randomized clinical trials extracted from the PubMed, Cochrane, EMBASE, and UpToDate databases. The search terms used were “continuous renal replacement therapy” and “intermittent renal replacement therapy,” excluding books, abstracts, and guidelines. Of the 218 articles initially identified, 11 met the eligibility criteria after screening and inclusion of additional sources. Results: The analysis showed no significant difference in mortality rates between CHD and IHD. However, CHD demonstrated a higher renal recovery rate and better cost-effectiveness in critically ill patients. Conclusion: These findings highlight CHD’s potential advantages in improving clinical and economic outcomes in acute renal failure management.